Pyramids or sandcastles? Regulating police conduct in Ireland. (20th October 2020) - Moss, Brian
ABSTRACT: Responsive regulation advances the idea that overseers should act cautiously against misconduct, imposing increasingly harsher methods in a phased approach depending on the response of the errant actor. Responsive regulation is assessed here in relation to the Irish policing model since 2007, seeking to determine whether it has been and remains a suitable way to deal with police misconduct that has emerged time and again in that jurisdiction. Using complaint data, it is argued that police overseer treatment of low-level and serious misconduct has not met the expectations of responsive regulation. Further, there has been no evident police commitment to distinguish praiseworthy police officer performance in line with a later version of responsive regulation. Both issues have implications for retention of responsive regulation as a guiding theory for continued police oversight and reform.